THE USE OF KOREAN WORDS BY NON-NATIVE SPEAKERS IN STIKES BANYUWANGI - Wirawati, Wahyu Adri (Universitas PGRI Yogyakarta, 2015)
ABSTRACT: Korean language has become one of the famous foreign languages in Indonesia. It entered Indonesia through their culture such as songs, movies and dramas. Indonesia people, in this study the students of STIKES Banyuwangi, learn the Korean language through subtitles given in every movie and drama, and also lyrics of a song. The subtitles are usually written in English or in bahasa Indonesia, while the lyrics of a song usually written in English, Hangul (Korean alphabet) and Korean language written in Latin alphabet. Using the subtitles and the lyrics, the Indonesia people can learn and use the Korean language. Nevertheless, their Korean language is not used appropriately because they do not understand the whole meaning of a conversation and the grammar and strucure of a sentence so they only use several words that have specific meaning. They acquire the words that usually appear in the subtitles and try to translate it into Bahasa Indonesia by using âGoogle Translateâ or dictionary. Most of the words are related to feeling and nickname in relationship. Yet, because there is still little number of people understanding Korean language, the Indonesian teenagers only use it with their peer who also like the Korean culture. They do not use it in a formal situation or in a situation when they know the person they speak to does not understand Korean language. When they speak in Korean language, code mixing appears. Entertainers, particularly singer, actor and actress, become the major factor that motivates the students to learn Korean language. It has influenced the students in STIKES Banyuwangi and as a result several of them use Korean words in their communication. Â Keywords: Korean language, words, language learning.